Interference Management in Heterogeneous Network With Particle Swarm Optimization - Rummi Sirait; Nifty Fath (IAES Indonesia Section, 2019)
In heterogeneous network, femtocell is deployedinside macrocell coverage. Femtocell and macrocell use thesame frequency as the resource. Thus, if the resources are notproperly allocated, the interference will arise. The higher levelof interference results in decreasing signal quality. Therefore,interference management is needed to increase networkcapacity and system performance. This research implementsparticle swarm optimization (PSO) algorithm to minimizeinterference on the heterogeneous network. Based on thesimulation results, it is shown that PSO algorithm worksefficiently to increase the throughput value of femto userequipment (femto UE) up to 62,2 Mbps by minimizing theinterference.